2014
DOI: 10.4314/ijbcs.v7i5.9
|View full text |Cite
|
Sign up to set email alerts
|

Étude de l’activité antifalcemiante et de la thermo- et photo-dégradation des anthocyanes de <i>Centella asiatica, Thomandersia hensii et Maesopsis eminii</i>

Abstract: ; trois plantes utilisées en médicine traditionnelle contre la drépanocytose dans la ville de Kisangani (RD Congo), a été testée en utilisant le test d'Emmel. Les résultats obtenus ont montré une activité antifalcémiante importante in vitro pour les trois plantes. Cette activité serait due aux anthocyanes. Les concentrations minimales de normalisation des drépanocytes obtenus sont de l'ordre de 8µg/ml pour les anthocyanes de ces trois plantes. Les spectres des anthocyanes ont montré une sensibilité à lumière U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 4 publications
2
14
0
Order By: Relevance
“…A similar result was already obtained for some medicinal plant species used for the management of SCD by Congolese traditional healers. This activity could be due to compounds easily extracted by the used polar solvents such as anthocyanins or to phenolic or triterpenoic acids as previously reported [13][14][15][16][17][18][19][20]23]. The treated SS RBCs demonstrated a remarkable similarity to normal blood values.…”
Section: Extraction Yieldsmentioning
confidence: 81%
See 2 more Smart Citations
“…A similar result was already obtained for some medicinal plant species used for the management of SCD by Congolese traditional healers. This activity could be due to compounds easily extracted by the used polar solvents such as anthocyanins or to phenolic or triterpenoic acids as previously reported [13][14][15][16][17][18][19][20]23]. The treated SS RBCs demonstrated a remarkable similarity to normal blood values.…”
Section: Extraction Yieldsmentioning
confidence: 81%
“…Fractions were filtered and concentrated to dryness under reduced pressure using a rotary evaporator. Extraction of anthocyanins was then done using 100 g of dried powdered plant material with acidified methanol (1% HCl) following an established protocol [13][14][15][16][17][18][19][20]. Anthocyanins extract was then defatted by n-hexane.…”
Section: Selection and Plant Materials Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fractions were filtered and concentrated to dryness under reduced pressure using a rotary evaporator. Extraction of anthocyanins was then done using 100 g of dried powdered plant material with acidified methanol (1% HCl) following an established protocol [13][14][15][16][17][18][19][20]. Anthocyanins extract was then defatted by nhexane.…”
Section: Extraction and Chemical Screeningmentioning
confidence: 99%
“…The control of a hemolytic disease such as malaria by the non human primates through medicinal plants based diet indicates that the plants consumed by these animals would be displayed anti-hemolytic and anti-inflammatory effects and could be beneficial for people suffering from SCD. Recently, our research team has investigated the antisickling activity of some Congolese plants used to treat SS anemia in Congolese traditional medicine and showed that anthocyanins are the main bioactive gents [13][14][15][16][17][18][19][20]. As several other flavonoids, anthocyanins are powerful free radical scavengers and show antioxidant activity [21][22].…”
Section: Introductionmentioning
confidence: 99%